Strengthening Madrasah Teachers' Competence in Enhancing Religious Moderation Understanding in West Nusa Tenggara - Lathifatul Maghfiroh; Mahmud Arif; Fakhrurozi (al-Afkar, Journal For Islamic Studies, 2025)
Understanding religious moderation is an important basis for instilling a sense of tolerance among Indonesian society, especially students. In this context, strengthening the understanding of religious moderation for madrasa teachers in NTB (West Nusa Tenggara) can be valuable additional knowledge in facing the contemporary era. The research used a qualitative method with a phenomenological approach and through an interview process involving the Director of teachers and education staff, the Head of the MI/MTS GTK Development Sub-Team, madrasah principals and madrasah teachers in NTB. This research was carried out directly in the implementation of activities in NTB, precisely one of the programs organized by the Indonesian Ministry of Religion. The main aim of this research is to strengthen the understanding and motivation of madrasa teachers in implementing religious moderation in the school environment. The findings in this research show that there are many cases that occur among NTB students which become the main problem in religious moderation, especially in terms of maintaining the values ​​of tolerance. The understanding obtained from this research becomes additional motivation for madrasa teachers in implementing religious moderation in the school environment. By increasing the understanding and strengthening the competency of madrasa teachers in religious moderation, it is hoped that they will be able to teach better values ​​of tolerance to their students. This will have a positive impact in building a society that is more harmonious, respectful of each other, and has an inclusive attitude towards differences in religion and belief.